How Important Is the Etiology in the Treatment of Epiphora? - Mahmut Oğuz Ulusoy; Sertaç Argun Kıvanç; Mehmet Atakan; Berna Akova-Budak (Journal of Ophthalmology)
Purpose. There are several etiological factors that cause epiphora, and treatment differs according to the cause. We aimed to evaluate the etiology of epiphora and the treatment modalities of the affected patients. Materials and Methods. Data of patients who were referred to ophthalmology clinics for epiphora were retrospectively analyzed. All patients were evaluated for epiphora etiology, treatment modalities, and duration of complaints, after complete ophthalmologic examination. Results. This study consisted of 163 patients with a mean age of 64.61 ± 16.52 years (range 1–92 years). Lacrimal system disease (48.4% [79/163]) was the most common cause, followed by ocular surface disease (dry eye/blepharitis) (38.7% [63/163]). Among the patients included in this study, 69% (113/163) did not receive any treatment, whereas only 1.8% (3/163) were treated surgically. About 4.3% of the patients (7/163) had a complaint for more than 5 years (p=0.012) and six of these had chronic dacryocystitis and one had ectropion. Conclusion. Epiphora not only has a negative impact on patients’ comfort, but also puts them at risk for probable intraocular operations in the future. Therefore, the wide range of its etiology must be taken into consideration and adequate etiology-specific treatment options must be applied.